Two-degree-of-freedom Grinding Wheel Profile Modification Manipulator and Its Error Compensation - Bin Yang; Xiaodi Huang; Yongcheng Huang (Jixie chuandong)
Compared with traditional grinding wheels，grooved grinding wheels have many advantages，but the error of grinding wheel profile has certain influence on machining accuracy. Therefore，a grinding wheel profile modification manipulator for CNC grinding machine is proposed，and a simple and economical method for alignment measurement and static error compensation of the manipulator is designed. The modification manipulator consists of two linear rails of the horizontal guideway and the vertical guideway. The guides are driven by a high-precision ball screw connected to a DC servo motor with optical encoder feedback. A single point diamond dressing tool is installed on the vertical guide rail. The alignment measurement method used a micrometer and a digital reading of the grinder. By measuring the contour error formed by the manipulator，the motion error compensation method is verified experimentally. The results show that the static error compensation method reduces the profile error of the grinding wheel by 40%，to the range of ±10 μm.